Empirical Analysis of Determinants, Distribution and Dynamics of Poverty - Kenneth Harttgen (Peter Lang International Academic Publishers, 2007)
Poverty and inequality persist in many dimensions in the developing world. In order to understand the determinants of poverty and its distribution between and within countries, it is necessary to know its dimensions and the channels through which poverty and inequality affect human well-being. This book analyzes the spatial disparities of the outcomes and determinants of poverty, the interdependencies of dimensions of poverty, the distribution of progress in human development over the population and the dynamics of poverty risk over time. The study takes into account the global spread of poverty. Based on cross-country comparisons of countries from Africa, Latin America, and South Asia, this study does not only consider on average outcomes and determinants of different indicators of human well-being, but also examines their distribution between and within countries.
Keywords: 330